Activation of liver X receptors inhibits experimental fibrosis by interfering with interleukin-6 release from macrophages - Beyer, Christian; Huang, Jingang; Beer, Juergen; Zhang, Yun; Palumbo-Zerr, Katrin; Zerr, Pawel; Distler, Alfiya; Dees, Clara; Maier, Christiane; Munoz, Louis; Krönke, Gerhard; Uderhardt, Stefan; et al. (Annals of the Rheumatic Diseases, 2015)
To investigate the role of liver X receptors (LXRs) in experimental skin fibrosis and evaluate their potential as novel antifibrotic targets.We studied the role of LXRs in bleomycin-induced skin fibrosis, in the model of sclerodermatous graft-versus-host disease (sclGvHD) and in tight skin-1 (Tsk-1) mice, reflecting different subtypes of fibrotic disease. We examined both LXR isoforms using LXR?-, LXR?- and LXR-?/?-double-knockout mice. Finally, we investigated the effects of LXRs on fibroblasts and macrophages to establish the antifibrotic mode of action of LXRs.LXR activation by the agonist T0901317 had antifibrotic effects in bleomycin-induced skin fibrosis, in the sclGvHD model and in Tsk-1 mice. The antifibrotic activity of LXRs was particularly prominent in the inflammation-driven bleomycin and sclGvHD models. LXR?-, LXR?- and LXR?/?-double-knockout mice showed a similar response to bleomycin as wildtype animals. Low levels of the LXR target gene ABCA-1 in the skin of bleomycin-challenged and control mice suggested a low baseline activation of the antifibrotic LXR signalling, which, however, could be specifically activated by T0901317. Fibroblasts were not the direct target cells of LXRs agonists, but LXR activation inhibited fibrosis by interfering with infiltration of macrophages and their release of the pro-fibrotic interleukin-6.We identified LXRs as novel targets for antifibrotic therapies, a yet unknown aspect of these nuclear receptors. Our data suggest that LXR activation might be particularly effective in patients with inflammatory disease subtypes. Activation of LXRs interfered with the release of interleukin-6 from macrophages and, thus, inhibited fibroblast activation and collagen release.
EVALuna2:12871